Ovarian incision enhances folliculogenesis: A rat model. Issue 10 (8th July 2020) - Takmaz, Ozguc; Asoglu, Mehmet Resit; Yuksel, Bahar; Gungor, Mete; Tokat, Fatma; Kayhan, Kerem Cavit; Ozaltin, Selin; Dogan, Murat; Buyru, Faruk; Bastu, Ercan
Abstract: Aim: To determine whether performing incision on the surface of the ovarian cortex in rats advances follicular development. Methods: Five to seven separate superficial incisions were performed on the surface of right ovaries of 6‐7–month‐old albino Wistar rats. Daily 40 IU of gonadotropins were administered for 14 days. On the 15th day, both ovaries of the rats were removed. The right (incised) ovaries were compared with the contralateral ovaries in terms of ovary's weight, numbers of primordial, primary, secondary and antral follicles, their mean percentages and mean Ki‐67 proliferation indices. Results: A total of 22 ovaries were evaluated, with 11 right ovaries (incised) and 11 left ovaries (non‐incised). The mean weight of ovaries was greater in the right ovaries than in the left ovaries; however, no statistical difference was found between them (0.77 ± 1.22 vs. 0.22 ± 0.08 gr, P = 0.159). The numbers of secondary and antral follicle were statistically higher in the right ovaries than in the left ovaries (4.4 ± 1.5 vs. 2.1 ± 1.6, P = 0.003 and 18.6 ± 8.7 vs. 11.3 ± 7.5, P = 0.046, respectively). The right ovaries also significantly differed from the left ovaries in terms of mean percentages of primordial and antral follicles ( P  < 0.05 for both). The mean Ki‐67 proliferation index had a marginal difference between the groups ( P = 0.064). Conclusion: Performing incisions on the surface of the ovarian cortex in rats may advance the ovarian follicular development. Future animal studies may provide more evidence regarding potential benefits of mechanical stimulation to the ovaries.